Fatty acid profile in male and female sex gray mullet (Liza aurata) in the southern shores of the Caspian Sea - M Norouzi; M Bagheri Tavani (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
The present study aimed to assess fatty acid profile in filet of male and female gray mullet from the southern region of the Caspian Sea. A total of 100 fish (55 male and 45 female) were caught from 10 stations in three coastal provinces of the Caspian Sea. Carcasses were analyzed according to the standard AOAC methods, and fatty acids were measured using gas chromatography. Mean protein, fat, moisture, and ash in golden gray mullet were 22.18±1.98, 3.08±1.21, 78.02±2, 1.40±0.43 respectively. A total of 28 fatty acids were identified, including 10 saturated, 8 monounsaturated, and 10 polyunsaturated fatty acids. Total amount of SFA fatty acids were 27.63, 24.95, 36.02 grams per 100 grams fat, respectively in male fish, and 30.39, 30.26, 29.42 grams per 100 grams fat respectively, in female fish, with a significant difference between them. The most prevalent SFA fatty acids included palmitic, oleic, and docosahexaenoic in fish muscles. Omega 3, omega 6, and omega 9 fatty acids in golden gray mullet comprised 29.61, 3.31, 11.17 percentage of total fatty acids respectively, and were significantly higher in the male species. ω-3/ω-6 and PUFA/SFA ratios were 9.22 and 1.2%, respectively. The sum total of two essential fatty acids in gray mullet (DHA and EPA) was 21.64%, which is important to promotion of health and prevention and recovery from illness in humans.